Crystal structure of 1,2-bis(4-fluorophenyl)-1-hydroxy-2,3,8-trimethoxyacenaphthene: formation of a five-membered intramolecular O—H...O hydrogen-bonded ring - Hiroaki Iitsuka; Kun Li; Miyuki Kobayashi; Kikuko Iida; Noriyuki Yonezawa; Akiko Okamoto (Acta Crystallographica Section E: Crystallographic Communications, 2021)
The structure of the title compound, C27H22F2O4, at 193 K has triclinic (P\overline{1}) symmetry. The hydroxy and methoxy groups at the 1,2-positions of the acenaphthene core display a cis configuration. Both substituents are involved in the formation of a five-membered intramolecular O—H...O hydrogen-bonded ring. The 4-fluorophenyl rings make dihedral angles of 87.02 (7) and 51.86 (8)° with the naphthalene ring system. In the crystal, a pair of non-classical C—H...O hydrogen bonds forms centrosymmetric dimeric structures. The dimeric aggregates are linked in the ac plane through non-classical C—H...F hydrogen bonds and C—H...π interactions.